COORDINATION PROTECTION SYSTEM DESIGN FOR INVERTER-BASED MICROGRID - Ikhsan Kusrachmansyah, Muhammad
In the inverter-based microgrid system, there is a problem with the small magnitude of short-circuit current contributed by the inverter. This happens because the components of the inverter, namely switches, which are usually IGBTs or MOSFETs, have a certain current limit that must not be exceeded to ensure the components are not being damaged. The fault current contributed by this inverter might be smaller than the conventional overcurrent relay pickup current which results in no fault being detected. An alternative solution to overcome this problem is to use a 51V relay which has a lower pickup current when detect a voltage drop. In this case, the writer designing and evaluating overcurrent protection, protection coordination, and the effect of using NGR in inverter-based microgrid systems. Tests were carried out using DIgSILENT Power Factory for several generation scenarios, fault impedance, and fault types. In conclusion the 51V relay is able to overcome the insensitivity of conventional overcurrent relays, the coordination between relays that had been carried out was good, and it is better not to use NGR in an inverter-based microgrid system.